BRAND APPEAL, EMOTIONAL ATTACHMENT, AND RESPONSIBLE CONSUMERISM: THE MEDIATING ROLE OF CONSUMER BEHAVIOR - Vika Aprianti; Sabilla Saberina; Johannes Kristian Siregar (Telkom University, 2026)
Growing awareness of environmental and social issues has encouraged consumers to adopt more responsible consumption practices. However, empirical evidence explaining how brand-related factors influence responsible consumerism remains limited, particularly in emerging markets. This study examines the influence of brand appeal and emotional brand attachment on responsible consumerism, with consumer behavior serving as a mediating variable. Data were collected from 238 consumers of eco-friendly products in urban areas of Indonesia using an online questionnaire with purposive sampling. Structural Equation Modeling (SEM) was applied to analyze the relationships among the constructs. The results show that brand appeal and emotional brand attachment significantly influence consumer behavior, which subsequently promotes responsible consumerism. In addition, consumer behavior plays a significant mediating role in translating brand perceptions and emotional connections into responsible consumption practices. These findings contribute to the literature by integrating emotional branding and consumer engagement perspectives in explaining responsible consumerism and provide strategic insights for developing sustainabilityoriented branding strategies